Estrategia de responsabilidad social empresarial de una terminal portuaria en Barranquilla, Colombia (2019)
The paper is the product of a research whose objective is to characterize the Corporate Social Responsibility actions that a Harbour Terminal practices to later propose corrective actions that help sustain this type of initiatives. The method of analysis was applied, with a qualitative, descriptive approach under a documentary, bibliographic design. After the data analysis, it was found that the company enjoys of an ethical framework based on corporate values and principles aligned to its economic activity, developing social actions from four pillars that respond to the social, economic and environmental dimensions, nevertheless, it is required to reinvigorate the interactive media and mass media instrumentation. As a conclusion, it is suggested that the Terminal must replicate the Bolívar and Sucre models that have made it worthy of distinctions, and integrate collective intelligence into its social responsibility strategy that allows it to develop competences in employees such as: cooperation, teamwork and the integrative approach.